Effect of microstructure on complex permittivity and microwave absorption properties of recycled α-Fe2O3 nanopowder prepared by high-energy ball milling technique - Mensah, Ebenezer Ekow; Abbas, Zulkifly; Azis, Raba’ah Syahidah; Khamis, Ahmad Mamoun (American Scientific Publishers, 2022)
This study was aimed at investigating the effect of microstructural variations on relative complex permittivity and microwave absorption properties of recycled α-Fe2O3, following application of high-energy ball milling technique to modify particles into nanopowder. Three portions of recycled α-Fe2O3 granules were separately milled for 8 h, 10 h and 12 h respectively and their microstructural characteristics were examined using X-ray diffraction (XRD), High-resolution transmission electron microscopy (HRTEM) and Brunauer-Emmett-Teller (BET) analysis. This was followed by relative complex permittivity and microwave absorption characterizations which were conducted at X-band microwave frequency range using the rectangular waveguide technique in connection with a vector network analyzer. Results established interfacial lattice defects and imperfections in the milled portions which became more pronounced with reduced crystallite sizes, and contributed to enhanced interfacial polarization process, leading to increased relative complex permittivity and microwave absorption properties of the recycled α-Fe2O3 nanopowders. The smallest estimated crystallite size of 11.1 nm was obtained after 12 h of milling with ɛ r = 12.1–0.46j at 8 GHz, which was reduced to ɛ r = 11.0–0.34j at 12 GHz while its power loss values varied between 18.3 dB and 23.3 dB in the 8–12 GHz range. A positive correlation was identified that connects microstructural variations with relative complex permittivity and power loss, and could be exploited to tune the microwave absorption properties of the recycled α-Fe2O3 particles.